Therapeutic efficacy of ivermectin, fenbendazole and albendazole against naturally occuring gastrointestinal nematodiasis infection in Black Bengal Goat of Bangladesh - Aktaruzzaman, Md.; Mirazul Islam, Md.; Mohamed, Zahurin; Siddiqul Islam, Md.; Matiar Rahman Howlader, Md. (International Journal of Biological Research, 2015)
This study aimed to evaluate the efficacy of ivermectin, fenbendazole and albendazole against gastrointestinal nematodes in naturally infected goats of government goat development farm, Sylhet, Bangladesh. The study included 50 black Bengal breed of which 30 were naturally infected and randomly selected 20 on the basis of their weight and egg count. Twenty black Bengal goats of 13-15 month old irrespective of sex infested with gastrointestinal nematodes were selected for this experiment and randomly divided into four equal groups (group A, B, C and D) where each group consisted of 5 goats and goats of group D were kept as control group. One injectable ivermectin (200 Âµgkg-1 body weight, S/C) preparations (Techno Drugs, Limited, Bangladesh) and two solid fenbendazole, albendazole (7.5 mgkg-1 body weight, orally) preparations (Techno Drugs, Limited and Square Pharmaceuticals Ltd, Bangladesh) were used for positive control of gastrointestinal nematodes as group A, B and C. Goats of group D was kept as control without giving any treatment. Before trials (day 0), total egg count, blood samples and initial body weight were recorded. During the study period the fecal and blood samples were collected directly from rectum and examined on 7th, 14th, 21st and 28th day using McMaster fecal egg counting method. Body weight was recorded on day 28 following the treatments. The therapeutic efficacy was evaluated through determination of parasitic prevalence, body weight gain/loss and hematological findings. Pre and post-treatment EPG (eggs per gram) values were recorded, and efficacies compared. The results showed that the efficacy of ivermectin was 100%, followed by fenbendazole 95.33% and albendazole 90.11%. The observed differences in efficacy between these three brands of anthelmintics were most likely due to variations either in quality or the administered doses. The body weight of the treated animals was slightly increased, which were significant (p<0.05). After treatment with ivermectin, fenbendazole and albendazole, Total Erythrocyte Count (TEC), Hemoglobin (Hb) content and Packed Cell Volume (PCV) were increased significantly (p<0.01 and p>0.05) in goats but Erythrocyte Sedimentation Rate (ESR) and Total Leukocyte Count (TLC) were decreased significantly (p<0.05 and p>0.01) in all treated goat and body weight was increased significantly (p<0.01) on day 28. The farm management practices along with results of the present study revealed the efficacy of multiple anthelmintics against gastrointestinal nematodiasis in goat. Additional detailed studies are required to clarify the current status of the efficacy of the anthelmintics widely used in different agro ecologies, animal species and livestock management systems in Bangladesh.